Acolhimento à demanda espontânea na atenção básica à saúde: uma análise a partir do 2º ciclo de avaliação externa do Programa Nacional de Melhoria do Acesso e da Qualidade da Atenção Básica - Lima, Edmilson Calixto de (2018)
The basic attention features receiving a huge variety of demand from users of the unified health system (SUS). To accompany the treatment offer comes the PMAQ, inserted in a context of the Federal Government, developing actions directed to improving access and quality in the SUS. Its objective is to evaluate the results of health policy. One of its tasks is to evaluate the greeting, constituted as a practice in the care relationship.In this paper, the focus is returned to the embracement of spontaneous demand.such demand is understood from any unscheduled care in Health Unit representing a momentary need of the user. However,the purpose of this work is to evaluate the spontaneous demand of the family health teams, based on data from the second cycle of the PMAQ-AB. It was observed that the South and Southeastern regions have achieved the highest levels of evaluation with respect to the realization of greeting, by contrast the North and northeast regions obtained the worst evaluations, having most unsatisfactory results or below the national average. The Central West region presented results distributed homogeneously, and neutral in this evaluation. It is concluded that each region should be considered according to your particularity , But that this study can serve as a guide in improvement of embracement in the basic attention of national health.